Pelatihan Google Classroom sebagai Bekal Teknik Pengajaran pada Mahasiswa Jurusan Pendidikan Agama Islam IAID Depok - Intyaswati, Drina; Ayuningtyas, Fitria; Prihatiningsih, Witanti (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
Online learning has become part of formal education. This learning process can produce efficiency in teaching and learning and foster a more exciting atmosphere. Using the Google Classroom application, teachers can apply their teaching and learning process through information technology-based media. Google Classroom training is conducted among students majoring in Islamic Religious Education from the Depok Islamic Religious Institute, where they will be prepared to become teachers/educators later. The results showed that the participants were enthusiastic about participating in the training to gain new teaching techniques that they did not previously possess, along with skills to become more familiar with the technology.